Integrating Importance-Satisfaction Model and Performance Evaluation Matrix to improve service quality - Chen, Shun-Hsing; Shun, Yu-Lan (Goodwood Publishing, 2023)
Purpose: The Taiwanese coffee market is growing every year, together with progressive changes in national habits and the concept of drinking coffee. This study examines a particular coffee studio and explores its service quality within a competitive environment as a basis for improvement. Research methodology: The design of service elements for the questionnaire was based on the relevant literature. The study identified 19 quality attributes as survey items, all of which were then subsumed under the Importance-Satisfaction Model (I-S Model) and Performance Evaluation Matrix (PEM) for service quality. Results: There are 8 service elements falling in “Excellent area,” 3 service elements falling in “To be improved area,” 3 service elements falling in “Surplus area,” and 6 service elements falling in “Care-free area” as shown by the results of Importance-Satisfaction Model introduction. With regard to the Performance Evaluation Matrix which are introduced later on, 2 service elements fall in “Priority improvement area,” 17 service elements fall in “Improvement area,” and 1 service element falls in “Maintenance area.” Limitations: The results of this study are only applicable to the analysis of the coffee studio survey, and cannot be extrapolated to explain improvements in service quality across the entire coffee industry. Contribution: It is expected that items in dire need of improvement can be confirmed by introducing a service quality model to enhance service quality, build a corporate image, and increase competitive advantage.